Stem cell impairment associated with type 2 diabetes mellitus : investigating the effects of obesity-associated inflammation on mesenchymal stem cell function - Seboko, Ascentia Mathapelo (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.